Supply Chain Management Efficiency Measurement Using Value Stream Mapping Method to Reduce Production Waste PT Tirta Investama - Permata, Nia Sastra; Suroso, Muhammad Suryo Panotogomo Abi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
PT Tirta Investama is a prominent Indonesian enterprise specialising in mineral water under the Aqua brand. This study aims to ascertain the nature of its waste using Value Stream Mapping methodology to assess supply chain management. A comparison of the current and future state maps shows how the Value Stream Mapping (VSM) method for measuring Supply Chain Management (SCM) has enhanced efficiency at PT Tirta Investama. The State Map showed that VA accounted for 40% of process time, and NVA accounted for 3,780 seconds. 60% of the process.By contrast, the Future State Map demonstrates a big increase in value-added activities (VA), which now account for 75% of total process time. Non-value-added activities (NVA) have dropped significantly to 25%.